Edukasi Budidaya Black Soldier Fly (BSF) dalam Rangka Menciptakan Lapangan Kerja Baru dan Solusi Permasalahan Sampah di Area Pasar Manis Ciamis - Hendar Nuryaman; Suprianto; Suyudi; Nur Arifah Qurota A’yunin (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
Waste becomes a problems if not managed properly, moreover comes from market activities whose are always there every day. Youth of Al Hilal live near "Pasar Manis" in Ciamis District, West Java, which some of the members do not have jobs. One of the activities in an effort to bring income is to cultivate the BSF (Black Soldier Fly), as a new breakthrough in providing cheap protein sources for animal feed and fish. This community service activity aims to provide education and management services for BSF cultivation in order to be able to utilize the economic potential of organic waste management and cultivation results. The method of activity is in the form of community education and BSF cultivation iptek with 34 participants. Generally, the results provide a new alternative to get income and improve skills in BSF cultivation so that is better in its management. Then an increase in understanding of the prospects, economic, social and environmental benefits so that it becomes an alternative solution in obtaining income and reducing the problem of organic waste in the surrounding area. The response of activities obtained by 88.2% greatly increases knowledge; 8.8% enough to add knowledge; and 2.9% are mediocre.